Concubines in court : marriage and monogamy in twentieth-century China - Tran, Lisa, 1973- (Rowman and Littlefield, 2015)
This groundbreaking book analyzes marriage and family reform in modern China. As the first in-depth study of the meaning and practice of monogamy and concubinage, Tran's work makes an important contribution to our understanding of Chinese society and legal norms. Poised at the intersection of Chinese history, women's history, and legal history, this book makes a significant contribution to all three fields.